Efektivitas Model Pembelajaran PBL dan PjBL Berbantuan Flipbook terhadap Kemampuan Berpikir Kritis Siswa - Mujiatun, Sri; Indiati, Intan; Siswanto, Joko (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
Critical thinking skills are important for students and need to be optimized. Optimization of students' critical thinking skills can be done by using appropriate learning models and learning media that are appropriate to the students' conditions. This study aims to determine the effectiveness of implementing Problem Based Learning and Project Based Learning models assisted by Flipbooks in improving students' critical thinking skills in science lessons. This study used a quasi-experimental method, with a sample of two experimental classes and one control class. The research data were analyzed using descriptive analysis and independent t-test. The results of the analysis showed an increase in students' critical thinking skills in science lessons with an average score of 87.7 in the experimental class which was significantly higher than the control class (81.8). In the indicators of explanation, interpretation, and evaluation abilities, the average score of students in the experimental class was significantly higher than the control class students, while in the indicators of analyzing and providing arguments there was no significant difference. Student responses to flipbook learning media also showed that 85% of students gave a very good response to both PjBL learning and PBL learning, because flipbook media can make science lessons more meaningful.